Endometrial HLA-F expression is influenced by genotypes and correlates differently with immune cell infiltration in IVF and recurrent implantation failure patients. Issue 8 (12th June 2022) - Papúchová, Henrieta; Saxtorph, Malene Hviid; Hallager, Trine; Jepsen, Ida E; Eriksen, Jens O; Persson, Gry; Funck, Tina; Weisdorf, Iben; Macklon, Nicholas S; Larsen, Lise Grupe; Hviid, Thomas Vauvert F
Abstract: STUDY QUESTION: Is human leukocyte antigen (HLA)-F protein expressed in mid-secretory endometrium, and are its expression levels influenced by HLA-F gene polymorphisms and correlated with the abundance of uterine natural killer (uNK) cells and anti-inflammatory M2 macrophages? SUMMARY ANSWER: HLA-F protein is expressed in mid-secretory endometrium, and levels are correlated with immune cell infiltration, plasma progesterone concentrations and HLA-F single-nucleotide polymorphisms (SNPs), however, women experiencing recurrent implantation failure (RIF) show differences when compared to women attending their first IVF treatment. WHAT IS KNOWN ALREADY: The immunomodulatory HLA class Ib molecules HLA-G and HLA-F are expressed on the extravillous trophoblast cells and interact with receptors on maternal immune cells. Little is known regarding HLA-F expression in endometrial stroma and HLA-F function; furthermore, HLA-F and HLA-G SNP genotypes and haplotypes have been correlated with differences in time-to-pregnancy. STUDY DESIGN, SIZE, DURATION: Primary endometrial stromal cell (ESC) cultures (n = 5) were established from endometrial biopsies from women attending IVF treatment at a fertility clinic. Basic HLA-F and HLA-G protein expression by the ESCs were investigated. A prospective controlled cohort study was performed including 85 women with a history of RIF and 36 control women beginning their first fertility treatment and with no history of RIF. In some analyses, the RIF group was divided into unknown cause, male infertility, female infertility, and both female and male infertility. Endometrial biopsies and blood samples were obtained the day equivalent to embryo transfer in a hormone-substituted cycle. PARTICIPANTS/MATERIALS, SETTING, METHODS: HLA protein expression by ESCs was characterized using flow cytometry and western blot. In the cohort study, the specific immune markers HLA-F and HLA-G, CD56 and CD16 (NK cells), CD163 (M2 macrophages), FOXP3 (regulatory T cells) and CD138 (plasma cells) were analysed by immunohistochemistry and a digital image analysis system in endometrial biopsies. Endometrial receptivity was assessed by an endometrial receptivity array test (the ERA ® test). Endometrial biopsies were examined according to modified Noyes' criteria. SNPs at the HLA-F gene and HLA-G haplotypes were determined. MAIN RESULTS AND THE ROLE OF CHANCE: HLA-F protein is expressed in the endometrium at the time of implantation. Furthermore, the HLA-F protein levels were different according to the womeńs HLA-F SNP genotypes and diplotypes, which have previously been correlated with differences in time-to-pregnancy. Endometrial HLA-F was positively correlated with anti-inflammatory CD163 + M2 macrophage infiltration and CD56 + uNK cell abundance for the entire cohort. However, this was not the case for CD56 + in the female infertility RIF subgroup. HLA-F levels in the endometrial stroma were negatively correlated with plasma progesterone concentrations in the RIF subgroup with known female infertility. Conversely, HLA-F and progesterone were positively correlated in the RIF subgroup with infertility of the male partner and no infertility diagnosis of the woman indicating interconnections between progesterone, HLA-F and immune cell infiltration. Glandular sHLA-G expression was also positively correlated with uNK cell abundance in the RIF subgroup with no female infertility but negatively correlated in the RIF subgroup with a female infertility diagnosis. LARGE SCALE DATA: Immunohistochemistry analyses of endometrial biopsies and DNA sequencing of HLA genes. Data will be shared upon reasonable request to the corresponding author. LIMITATIONS, REASONS FOR CAUTION: The control group of women attending their first IVF treatment had an anticipated good prognosis but was not proven fertile. A significant age difference between the RIF group and the IVF group reflects the longer treatment period for women with a history of RIF. The standardization of hormonal endometrial preparation, which allowed consistent timing of endometrial and blood sampling, might be a strength because a more uniform hormonal background may more clearly show an influence on the immune marker profile and HLA class Ib levels in the endometrium by other factors, for example genetic polymorphisms. However, the immune marker profile might be different during a normal cycle. WIDER IMPLICATIONS OF THE FINDINGS: The findings further highlight the importance of HLA-F and HLA-G at the implantation site and in early pregnancy for pregnancy success. Diagnostic measures and modulation of the complex interactions between HLA class Ib molecules, maternal immune cells and hormonal factors may have potential to improve fertility treatment. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by the Region Zealand Health Sciences Research Foundation and the Zealand University Hospital through the ReproHealth Research Consortium ZUH. The authors declared there are no conflicts of interest.